Anaesthesia recommendations for patients suffering from Alkaptonuria - Kastsiuchenka, Siarhei; Gerçek İrban, Arzu; Ranganath, Lakshminarayan; Davidson, John (Aktiv Druck & Verlag GmbH, 2014)
Alkaptonuria (AKU) is a rare autosomal recessive disorder with an incidence of 1:250 000 to 1:1000 000 live births. AKU is caused by a deficiency of the enzyme homogentisate 1,2-dioxygenase (HGO). This enzyme converts homogentisic acid (HGA) to maleylacetoacetic acid in the tyrosine degradation pathway. Accumulated HGA is rapidly cleared in the kidney and excreted in the urine. HGA blood levels are kept very low through rapid kidney clearance, but over time HGA is deposited in cartilage throughout the body and converted to a pigment-like polymer. This occurs through an enzyme-mediated reaction in collagenous tissues like ligaments, tendons, cartilage, and sclera.
Keywords: Alkaptonuria; Patients Suffering; Anaesthesia